Learning Strategies at SMP Muhammadiyah 5 Ngoro during the Covid-19 Pandemic - Faruq Iqbal Maulana (Proceedings of The ICECRS, 2021)
The aim of this study was to analyze the implementation effectiveness of the learning from home (BDR) process during the Covid-19 pandemic in of SMP Muhammadiyah 5 Ngoro. This research used mix method. The data collection technique used was a questionnaire given the students once a month. The subjects of this study were the students of SMP Muhammadiyah 5 Ngoro.Based on the results of research conducted by filling out questionnaires, in general, the implementation of learning from home (BDR)students of SMP Muhammadiyah 5 Ngoro run quite effectively with a percentage of 60-79%. The results of the BDR learning implementation questionnaire which had bad effectiveness with the criteria of 48% were in the evaluation process. It is suggested in learning from home (BDR), teachers are required to be able to design learning activities from planning to evaluating in a simpler, more creative and effective way.